Comparison between Eugenol in Essential Oil from Cinnamon Leaves (Cinnamomum verum) and Clove (Eugenia caryophyllata) Extracted by Soxhlet Extraction - Murugananthan, Yuggheshinie; Nor Faizah Binti Razali,; Sity Aishah Binti Mansur, (Progress in Engineering Application and Technology, 2022)
Essential oil from the flowers is too expensive and it causes people to consume fragrance oil for various application. Usage of fragrance oil can bring harm to human health. This study is conducted to produce essential oil from spices that can be inexpensive as spices are cheap and available at all seasons. The essential oils from clove (Eugenia caryophyllata) and cinnamon leaves (Cinnamomum verum) contain secondary metabolites that are volatile and widely used in various industry. In this study, it was aimed to extract the essential oil from clove and cinnamon leaves, as well as conducting analytical assay such as thin layer chromatography and Fourier transform infrared spectroscopy to determine the presence of the constituent and to characterize eugenol respectively. Extraction of essential oil was extracted using Soxhlet extraction method using ethanol 95% for 3 and 5 hours from clove bud and cinnamon leaves and removal of solvent was done with rotary evaporator at 40℃. Extraction of essential oils from clove (Eugenia caryophyllata) for 3 hours extraction and 5 hours extraction have the percentage of yield of 0.266% and 0.363% respectively. Extraction of essential oil from cinnamon leaves (Cinnamomum verum) for 3 hours extraction and for 5 hours extraction has the percentage of yield of 0.0938% and 0.247% respectively. The essential oil extracted from clove for 5 hours has the highest yield. The presence of constituent has been identified by thin layer chromatography analysis that was conducted by using a solvent of petroleum ether, toluene, and ethyl acetate with a ratio of 7:2:1. In the analysis of Fourier transform infrared spectroscopy, the functional group of eugenol has been identified in all the samples. By comparing the transmittance percentage, it can be concluded that the clove extract extracted for 5 hours have the higher concentration of functional group of eugenol. In conclusion, the research has helped to establish that using clove oil as essential oil rather than the use of fragrance oil is far more cost-effective and beneficial.